Recycling WEEE: Polymer characterization and pyrolysis study for waste of crystalline silicon photovoltaic modules. (February 2017) - Dias, Pablo; Javimczik, Selene; Benevit, Mariana; Veit, Hugo
Highlights: Optimum pyrolysis duration was determined using statistical analysis. TGA was used to determine optimum pyrolysis temperature. Particle size influence on pyrolysis was tested. Polymer matter from silicon PV modules were characterized. Abstract: Photovoltaic (PV) modules contain both valuable and hazardous materials, which makes its recycling meaningful economically and environmentally. In general, the recycling of PV modules starts with the removal of the polymeric ethylene-vinyl acetate (EVA) resin using pyrolysis, which assists in the recovery of materials such as silicon, copper and silver. The pyrolysis implementation, however, needs improvement given its importance. In this study, the polymers in the PV modules were characterized by Fourier transform infrared spectroscopy (FTIR) and the removal of the EVA resin using pyrolysis has been studied and optimized. The results revealed that 30 min pyrolysis at 500 °C removes >99% of the polymers present in photovoltaic modules. Moreover, the behavior of different particle size milled modules during the pyrolysis process was evaluated. It is shown that polymeric materials tend to remain at a larger particle size and thus, this fraction has the greatest mass loss during pyrolysis. A thermo gravimetric analysis (TGA) performed in all polymeric matter revealed the optimum pyrolysis temperature is around 500 °C. Temperatures above 500 °C continue to degrade matter, but mass loss rate is 6.25 times smaller. This study demonstrates the use of pyrolysis can remove >99% of the polymeric matter from PV modules, which assists the recycling of this hazardous waste and avoids its disposal.